2010
DOI: 10.1111/j.1747-0803.2010.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Cerebral Oxygenation Following Repair of Tetralogy of Fallot: The Effects of Converting From Positive Pressure Ventilation to Spontaneous Breathing

Abstract: We conclude that converting from positive pressure ventilation to spontaneous negative pressure breathing following repair of TOF significantly improves arterial blood pressure and cerebral oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…It has been proposed that cardiac output in patients after TOF repair can be augmented by conversion of positive pressure ventilation to either negative pressure ventilation or spontaneous breathing [1,2,17]. The diastolic pulmonary arterial flow is sensitive to changes in intrathoracic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that cardiac output in patients after TOF repair can be augmented by conversion of positive pressure ventilation to either negative pressure ventilation or spontaneous breathing [1,2,17]. The diastolic pulmonary arterial flow is sensitive to changes in intrathoracic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Since diaphragmatic descent increases intra-abdominal pressure, these combined effects cause decreased right atrial pressure and increased venous pressure in the abdomen, markedly increasing the pressure gradient for systemic venous return [23]. Furthermore, the greater the decrease in ITP, the greater the increase in LV afterload for a constant arterial pressure, and right ventricle stroke output increases [24]. Pulmonary edema from negative pressure effect in patient breathing through the narrow endotracheal tube could also contribute to lower ITP.…”
Section: Physiology Of Spontaneous Breathing Trialsmentioning
confidence: 99%
“…Some studies found that negative pressure ventilation following corrective surgery of TOF was associated with improved blood pressure [4,5]. In the present study, PEEP was set at between 2 and 8 cmH 2 O, and the tidal volume between 8 and 10 mL/kg during preoperational ventilation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative negative-pressure ventilation improved the stroke volume and cardiac output by more than 45%, and reduced the systemic and pulmonary vascular resistances [4]. Converting from positive pressure ventilation to spontaneous negative pressure breathing following repair of TOF also improved arterial blood pressure and cerebral oxygenation [5]. There has been little information on the relations between preoperational mechanical ventilation and the postoperative outcomes of TOF repair.…”
Section: T Etralogy Of Fallot (Tof) Is a Common Cyanotic Congen-mentioning
confidence: 99%